2014
DOI: 10.1074/jbc.m114.562116
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Allosteric Hot Spots in the Transmembrane Domains of Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Channels and Multidrug Resistance Protein (MRP) Pumps

Abstract: Background: Multidrug resistance proteins (MRPs) and the cystic fibrosis transmembrane conductance regulator (CFTR) are thermodynamically distinct ATP-binding cassette (ABC) transporters. Results: Structural elements that couple ATP binding to channel opening in the CFTR channel also facilitate MRP drug export. Conclusion: MRPs and CFTR share components of a conserved activation mechanism. Significance: Allosteric hot spots suggest mechanistic similarities between thermodynamically distinct ABC transporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 66 publications
4
46
0
Order By: Relevance
“…Methods used for construction of the Yor1 mutants and analysis of oligomycin sensitivity were previously described (15). For analysis of Ycf1 mutations, the knockout strain (ycf1‐Δ0) from the Research Genetics (Huntsville, AL, USA) Saccharomyces cerevisiae gene deletion collection (23) was transformed by the polyethylene glycol method (24) with plasmids expressing Ycf1p alleles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods used for construction of the Yor1 mutants and analysis of oligomycin sensitivity were previously described (15). For analysis of Ycf1 mutations, the knockout strain (ycf1‐Δ0) from the Research Genetics (Huntsville, AL, USA) Saccharomyces cerevisiae gene deletion collection (23) was transformed by the polyethylene glycol method (24) with plasmids expressing Ycf1p alleles.…”
Section: Methodsmentioning
confidence: 99%
“…The evolutionary relationship between MRP pumps and the CFTR channel implies that they may use similar mechanisms for coupling ATP binding at the NBD dimer interface to those conformational changes in the TMs that underlie active substrate transport (MRPs) or channel gating (CFTR). Recently we discovered gain of function (GOF) mutations at conserved locations near the cytosolic bases of TMs 6 and 9 in CFTR and in the short MRPs (14, 15). These GOF mutations promoted ATP‐free CFTR channel activity, increased the ATP sensitivity of CFTR gating, and reversed the low ATP sensitivity of a CFTR construct with an NBD2 mutation that disrupts ATP binding.…”
mentioning
confidence: 99%
“…Conversely, VX-809 stabilization of MSD1 is postulated to improve maturation by enhancing stabilizing interactions with MSD2 and NBD1 (62). Gain-of-function mutations, which presumably stabilize an open conformation, have been identified in both MSD1 and MSD2 (63,64). It has also been suggested that low temperature rescue may be an NBD2-related effect (58), which does not occur in the absence of NBD2.…”
Section: Discussionmentioning
confidence: 99%
“…zebrafish, mouse, rat, rabbit, ferret, pig), although each has limitations regarding ease of use or degree to which human disease is recapitulated [35,36]. Finally, yeast phenomic screening has emerged as a means for discovery of gene-gene interaction networks and other features of CFTR class II and III variants [37,38,39], including identification and targeting of novel CFTR modulators in patient-derived epithelia [40]. …”
Section: Recent Advances In Model Systemsmentioning
confidence: 99%